Detection of SARS-CoV-2 and other human enteric viruses in wastewater from Gothenburg - Norder, Helene; Nyström, Kristina; Patzi Churqui, Marianela; Tunovic, Timur; Wang, Hao (University of Gothenburg, 2023)
Introduction to dataset

The dataset is part of a research study lead by adjunct professor Heléne Norder and colleagues at Gothenburg University and the Clinical Microbiology Laboratory at Sahlgrenska University Hospital and at the Gryaab wastewater treatment plant in Gothenburg.

The group has collected weekly wastewater sample from the Gryaad wastewater treatment plant in Gothenburg during multiple periods over the last 10 years. The latest collection period began in February 2020 and is ongoing, though with a few weeks break between November 2022 and January 2023. The present dataset includes the weekly results related to virus detection and quantification during this latest collection period. There was an initial focus on SARS-CoV-2, and data is available for SARS-CoV-2 from February 2020. Sampling related to the detection and quantification of other viruses started in week 2 of 2023. The other viruses considered include Pepper Mild Mottle virus (PMMoV), norovirus GG2 (winter vomiting virus), sapovirus, enterovirus, astrovirus, and adenovirus. More viruses will be added as new technologies are developed or if an outbreak caused by another virus is imminent. We type all viruses that increase in abundance in wastewater by sequencing, as we did for SARS-CoV-2 during the pandemic.

The data is updated weekly and can be downloaded from: https://blobserver.dckube.scilifelab.se/blob/wastewater_data_gu_allviruses.xlsx. A dashboard containing more information about the research, as well as data visualisations that are updated weekly is available on the Swedish COVID-19 and Pandemic Prepredness Portal. More data will be added over time: https://www.covid19dataportal.se/dashboards/wastewater/covid_quant_gu/

Wastewater treatment plant

Gryaab receives wastewater from a population of approximately 790,000 inhabitants in Gothenburg and surrounding municipalities such as Ale, Härryda, Kungälv, Lerum, Mölndal, and Partille as well as from industry, and rain and stormwater from the older parts of Gothenburg.

Research methodology

Since the flow of wastewater varies greatly depending on rainfall or snowmelt, the volumes of the weekly wastewater samples to be analyzed for viruses are flow-weighted and vary in volume between 1l and 15l. The reason for flow-weighted samples is to ensure that the same amount of wastewater from each household is analyzed each week. Several sensitive in-house techniques have been developed to concentrate virus in such large sample volumes.The first technique we developed involved the precipitation of viruses in wastewater with powdered milk (Hellmér et al., 2014 (https://journals.asm.org/doi/10.1128/AEM.01981-14) ). This technique was not suitable for detecting viruses in drinking water, because for this we needed to analyze several hundred liters of water. Therefore, we developed another technique that binds the virus to a membrane (Wang et al., 2020a (https://pubmed.ncbi.nlm.nih.gov/31590036/) ), through which very large volumes of water can pass. This technique was later also used to concentrate viruses in incoming and treated wastewater (Wang et al., 2020b (https://journals.asm.org/doi/full/10.1128/AEM.02073-20) ). This latter technique was also found to be sensitive for detecting SARS-CoV-2. Because these techniques are labor intensive and technically demanding, new techniques are still being developed in the laboratory to facilitate the method while maintaining sensitivity.

Nucleic acids were extracted from 1ml of concentrate and RT-qPCR technique or qPCR is used (depending on the nucleic acid of the virus to be detected, RNA or DNA) for detection and quantification of the virus. Primers used to detect the different viruses can be found in Hellmér et al. (2014) (https://journals.asm.org/doi/10.1128/AEM.01981-14) , Wang et al. (2020b) (https://journals.asm.org/doi/full/10.1128/AEM.02073-20) , and Saguti et al. (2021) (https://www.ncbi.nlm.nih.gov/pmc/articles/PMC7654368/) .

Metagenomics is also used to investigate the presence and spread of viruses that cause disease in humans or animals, but are not necessarily diagnosed. Several viruses that cause gastroenteritis and can cause neurological complications have already been identified, some of which are now included in routine diagnostics at the Clinical Microbiology Laboratory. For the other viruses, the technology for detection has been developed and can be used if there are smaller or larger outbreaks that are not caused by the commonly diagnosed viruses.
Keywords: Environmental epidemiology; Public health not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Health Sciences; Hälsovetenskap